2015
DOI: 10.1007/s40265-015-0365-2
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Analgesia and Novel Strategies for the Prevention of Chronic Post-Surgical Pain

Abstract: Chronic post-surgical pain (CPSP) is a serious complication of major surgery that can impair a patient's quality of life. The development of CPSP is a complex process which involves biologic, psychosocial, and environmental mechanisms that have yet to be fully understood. Currently perioperative pharmacologic interventions aim to suppress and prevent sensitization with the aim of reducing pain and analgesic requirement in acute as well as long-term pain . Despite the detrimental effects of CPSP on patients, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 106 publications
(126 reference statements)
1
57
0
1
Order By: Relevance
“…[32] A comprehensive systematic review for the prevention of chronic pain after surgery in adults identified ketamine as the most reliable pharmacological agent for the prevention of CPSP.…”
Section: Economic Impact From the Development Of Chronic Postsurgicalmentioning
confidence: 99%
“…[32] A comprehensive systematic review for the prevention of chronic pain after surgery in adults identified ketamine as the most reliable pharmacological agent for the prevention of CPSP.…”
Section: Economic Impact From the Development Of Chronic Postsurgicalmentioning
confidence: 99%
“…gabapentin and pregabalin, α 2 δ subunit voltage-dependent calcium channel blockers) may prove to be a useful tool in the postdischarge time period with patients struggling from prolonged moderate-to-severe acute postsurgical pain. 51 In a recent systematic review, even though results between the studies included were heterogeneous at 3 month follow-up, pregabalin was proposed to have an effect with respect to modifying postsurgical pain trajectories and reducing the development of chronic postsurgical pain. 52 However, in light of a recent publication demonstrating that several cohorts of patients did not experience the preventive effect for pregabalin on chronic post surgical pain (CPSP) 53 and the evidence we present herein, this conclusion needs to be reassessed.…”
Section: Discussionmentioning
confidence: 99%
“…57 This emerging literature suggests that patients should be screened before surgery for psychological vulnerabilities, and based on the results, psychological interventions, in addition to multimodal preventive analgesic strategies such as the ones implemented in this trial, should become a mainstay for perioperative postsurgical care. 51 This is the first study to compare the efficacy of pregabalin vs placebo for recovery of physical function at three time points (baseline, 6 weeks, and 3 months) for patients undergoing total hip arthroplasty. Although negative for such outcomes, a reduction in cumulative 24 h opioid consumption and superior pain relief for 1 week postdischarge was evident.…”
Section: Discussionmentioning
confidence: 99%
“…These pain management strategies of unimodal opioid administration for donor hepatectomy patients might result in suboptimal analgesic effectiveness that can introduce compromising adverse effects (AEs) and further predispose these patients to the potential of prolonged postoperative pain. Therefore, analgesic alternatives and other supplemental pain management strategies need to be considered (11). Postoperative liver dysfunction and the potential for compromised coagulation effectiveness can be an outcome from liver resection surgery.…”
mentioning
confidence: 99%